(untitled) (Global Journal of Science Frontier Research, 2012)
This research project was conducted to study the possibility of using calcite powder as a calcium supplement for livestock feeding. Samples of calcite powder procured from different parts of India were analyzed for dry matter (DM), total ash, acid insoluble ash and major and trace minerals using Atomic Absorption Spectrophotometer followed by determination of ruminal solubility of calcium carbonate, calcite, dolomite, lime stone powder and di-calcium phosphate powder as source of calcium. The results showed that samples of calcite powder procured from different parts of India, varied in Ca content (%) from 39.0 to 41.3 with an average of 40.03 ± 0.27%. These values were comparable to the Ca content of calcium carbonate samples ± 0.3%). However, P and Mg contents of calcite powder were higher than that of calcium carbonate. Mn content of both the calcium sources was similar, but Cu and Zn contents of calcite powder were higher than in calcium carbonate. Levels of toxic minerals like lead and cadmium were lower in calcite powder than in calcium carbonate but the fluorine content in the later was lower than in calcite powder indicating that calcite powder has the potential to be used as a source of calcium in the animal ration.